Simulation programme for oil palm LAI and yield prediction - Wan Ismail, Wan Ishak; Awal, Md Abdul; Endan, Johari; Harun, Mohd. Haniff (2005)
Computer simulation models have become an alternative source of information and replacing or enhancing information derived from costly and arduous field experiments, specially like oil palm where filed experiment are expensive, time consuming and laborious. Relatively there are little attempts to develop mechanistic models to simulate or forecast oil palm yield. A computer simulation model was developed using Visual C++ for simulation of leaf area index, radiation interception and yield of oil palm. Light interception was modelled using a modified Monsi-Saeki equation. Leaf area index and growth were modelled based on OPSIM approach (Kraalingen, 1985). The growth rate was assumed under ample supply of water and nutrients, in a pest, disease and weed free environment under the prevailing weather conditions. Therefore the rate of dry matter accumulation was a function of radiation interception, temperature and crop characteristics. Simulation results show that leaf area index had a large effect on radiation interception and a significant linear relationship with gap fraction. A significantly relationship was found between the simulated leaf area index and simulated yield, and actual LAI. The simulated LAI can be integrated with the photographic LAI for forecasting the oil palm yield.